Hemorragia intraventricular en el Hospital Infantil de Morelia "Eva Sámano de López Mateos" - Salmerón Gómez, Gessen (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
Embryonic development of the central nervous system Determinants that occur in the early stages of development can have fatal consequences for the newborn's nervous system, and often occur before knowledge of pregnancy. Embryonic period In the first 14 days after conception, the first stages of embryonic development are produced, which include the unicellular embryo, the morula, the blastocyst, the implantation process, and the development of the amniotic cavity and the umbilical vesicle of the embryo. fixation period, formation of the chorionic villi and the formation of the axial structure. By day 16 by means of autoradiography methods, the place of the future neural plate can be identified and by day 18 the neural furrow is already observed; When the facial cranial length begins neurulation, induced by the notochord and the adjacent mesoderm, the neuronal plate forms an ectodermal thickening zone that will lead to the brain and spinal cord. Between 20 and 21 days, the neural groove is formed in the center of the embryo with neural folding on each side. As it fuses the most cranial areas of the neural fold, the neuronal crest forms on both sides of the neural tube, from the ectodermal cells. These cells that form the ridge will migrate shortly after the neural tube closes and will become cells of the sensitive, sympathetic and parasympathetic ganglia, chromaffin cells of the adrenal medulla: cutaneous melanocytes, enteric neurons and facial connective tissue. On days 24 and 25, the closure of the neural tube has occurred cranially to the area of ​​the quadrilateral tubers and continues cephalad and caudal.

Desarrollo embrionario del sistema nervioso central Determinantes circunstancias que se producen en las primeras fases del desarrollo pueden tener consecuencias fatales para sistema nervioso del recién nacido, y a menudo tiene lugar antes de tener conocimiento del embarazo. Periodo embrionario En los primeros 14 días tras la concepción, se produce las primeras fases del desarrollo embrionario, que incluyen el embrión unicelular, la mórula, el blastocito, el proceso de implantación, y el desarrollo de la cavidad amniótica y de la vesícula umbilical del periodo de fijación, la formación de las vellosidades coriónicas y de la formación de la estructura axial. Al día 16 mediante métodos de autorradiografía ya se puede identificar el lugar de la futura placa neural y hacia el día 18 ya se observa el surco neural; cuando la longitud cráneo facial se inicia la neurulación, inducido por la notocorda y el mesodermo adyacente, se forma el plato neuronal una zona de engrosamiento ectodérmico que dará lugar al cerebro y la medula espinal. Entre los 20 y 21 días, se forma el surco neural en el centro del embrión con plegamiento neural a cada lado. A medida que va fusionando las zonas más craneales de los plegamientos neurales, se forman la cresta neuronal a ambos lasos del tubo neural, a partir de las células ectodérmicas. Estas células que forman la cresta migrarán poco después de que el tubo neural se cierre y se convertirán en células de los ganglios sensitivos, simpáticos y parasimpáticos, células cromafines de la medula suprarrenal: melanocitos cutáneos, neuronas entéricas y tejido conjuntivo facial. Hacia los días 24 y 25, el cierre del tubo neural se ha producido cranealmente hasta la zona de los tubérculos cuadrigéminos y continúa en sentido cefálico y caudal.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Pediatría
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4152; info:eu-repo/classification/cti/3; FCMB-E-2011-0052; Hemorragia; Intraventricular; Niños